2018
DOI: 10.3390/ijms19123776
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Plants and Plant Derived Phytochemicals against Acetaminophen-Induced Liver Injury

Abstract: Acetaminophen (APAP), which is also known as paracetamol or N-acetyl-p-aminophenol is a safe and potent drug for fever, pain and inflammation when used at its normal therapeutic doses. It is available as over-the-counter drug and used by all the age groups. The overdose results in acute liver failure that often requires liver transplantation. Current clinical therapy for APAP-induced liver toxicity is the administration of N-acetyl-cysteine (NAC), a sulphydryl compound an approved drug which acts by replenishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 204 publications
(217 reference statements)
3
47
0
2
Order By: Relevance
“…Asiatic acid (20) is a naturally occurring aglycone of ursane-type pentacyclic triterpenoids. It has been previously reported from a wide range of plants e.g., Actinida argute roots, Centella Asiatica leaves, and Combretum laxum Stems [ 43 ]. It has poly-pharmacological properties like antioxidant, anti-inflammatory.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asiatic acid (20) is a naturally occurring aglycone of ursane-type pentacyclic triterpenoids. It has been previously reported from a wide range of plants e.g., Actinida argute roots, Centella Asiatica leaves, and Combretum laxum Stems [ 43 ]. It has poly-pharmacological properties like antioxidant, anti-inflammatory.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Numerous in vivo and in vitro studies reported that asiatic acid (20) influences many enzymes, receptors, growth, and transcription factors, in addition to several cell signaling cascades. Moreover, it inhibits both HIV-1 and enterovirus 71 (EV71) replications in acutely infected host cells with IC 50 equal to 9 and 20 µM, respectively [ 43 , 44 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When APAP is uses as the dose of a physician, it is effective and nontoxic analgesic and antipyretic. Nevertheless, long term administration or overdoses of APAP can cause a deleterious effect on the liver [ 6 ]. APAP-induced liver injury was well recognized by numerous studies- [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
“…Overdose of APAP may cause a wide range of adverse effects [40,41]. Although quite a number of compounds (e.g., silymarin, glycyrrhizic acid and oleanolic acid) were shown to possess hepatoprotective effect against APAP-induced hepatotoxicity [42], their hepatoprotective effects and mechanisms of action might not be satisfactory enough, and administration of NAC is still one of the best clinical therapies for APAP-induced liver toxicity. Our study demonstrated that AS almost completely prevented APAP-induced liver injury as NAC in every aspect, and the hepatoprotection is associated with its retaining expression of CYP enzymes and inhibition of the activities of CYP2E1 and CYP3A11 to decrease APAP bioactivation.…”
Section: Discussionmentioning
confidence: 99%